Tazkiyat Al-Nafs Dalam Perspektif Al-Ghazali Dan Ibnu Miskawayh: Studi Komparatif Pembentukan Karakter Mulia - Moch. Bashori Alwi; Akhmad Ali Said; Misbachul Munir; Bayu Fermadi; Aina Noor Habibah; Moh. Hasan Fauzi; Yuni Pangestutiani; M. Romadhon (Journal of Innovative and Creativity, 2023)
This comparative analytical study examines the philosophical and pedagogical frameworks of tazkiyat al-nafs (purification of the soul) as conceptualized by two preeminent Islamic thinkers: Abu Hamid al-Ghazali (d. 505/1111) and Abu Ali Ahmad ibn Muhammad Miskawayh (d. 421/1030). Through rigorous examination of their foundational ethical treatises, particularly Al-Ghazali's Ihya' 'Ulum al-Din and Miskawayh's Tahdhib al-Akhlaq, this study elucidates the theoretical underpinnings, methodological approaches, and practical implications of their respective models for character formation. The analysis reveals a fundamental dichotomy between Miskawayh's rationalist-philosophical emphasis on psychic equilibrium and virtue cultivation through habituation, and Al-Ghazali's mystical-spiritual orientation toward divine proximity through systematic purification of the self. While both thinkers operated within the Aristotelian framework of virtue ethics and drew upon the tripartite division of the soul, their divergent epistemological commitments—Miskawayh's prioritization of natural reason and environmental conditioning versus Al-Ghazali's integration of Sufi mysticism with ethical praxis—produced substantively distinct architectures for moral development. This comparative investigation contributes to contemporary discourse on holistic character education within Islamic contexts, demonstrating the continued relevance of classical Islamic ethical philosophy for addressing multifaceted challenges in character formation and spiritual development.